Pattern of macrovascular disease phenotypes amongst newly diagnosed type 2 diabetic patients in a rural institute in Uttar Pradesh, India - Verma, Vijay Kumar; Singh, P. S.; Yadav, R. K.; Kumar, Manoj; Zafar, K. S.; Rawat, Ramakant (International Journal of Research in Medical Sciences, 2017)
Background: The objective of current study was to determine the proportion of Macrovascular Disease (MVD) phenotypes amongst newly diagnosed type 2 diabetic patients in our institute by dividing the cases into sub-groups according to the MVD sites involved (NMVD - no macrovascular disease; NSCS - non-significant carotid stenosis; CBVD - cerebrovascular disease; CAD - coronary artery disease; PAD - peripheral artery disease; PVD - polyvascular disease) and studying the anthropometric, clinical and laboratory parameters in each group. Methods:The study included a cohort of 136 newly diagnosed patients with T2 DM. Demographic, clinical and laboratory parameters were included in analyses. Standardized procedures were used to assess the risk factors of associated metabolic syndrome (MetS). Results:The proportion of patients with MVD was 27.94% amongst the participants in the study. The majority of patients with MVD were in the CAD group (15.44%). Age, male sex and smoking history were independent risk factors in the CAD and PAD groups (P <0.01). A low HDL-C value was an independent risk factor in the CAD and PVD group P = 0.03). Very high frequencies of MetS were observed in the PAD and PVD groups (90% and 91.7% respectively). Prevalence of PVD was three times more common in males as compared to that in females. All patients with PAD had associated CAD also. Conclusion: This study projects a high proportion of MVD amongst newly diagnosed Type 2 diabetics in rural sub-population in Uttar Pradesh. High rates of mortality and morbidity in these patients due to macroangiopathy warrant early screening of MVD to ensure timely preventive and therapeutic measures.